Ischemia From Nonculprit Stenoses Is Not Associated With Reduced Culprit Infarct Size in Patients with ST-Segment–Elevation Myocardial Infarction. (6th May 2021) - Ekström, Kathrine; Nielsen, Julie V.W.; Nepper-Christensen, Lars; Ahtarovski, Kiril A.; Kyhl, Kasper; Göransson, Christoffer; Bertelsen, Litten; Ghotbi, Adam A.; Kelbæk, Henning; Høfsten, Dan E.; Køber, Lars; Schoos, Mikkel M.; et al.
Abstract : Background: In patients with ST-segment–elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention, reperfusion injury accounts for a significant fraction of the final infarct size, which is directly related to patient prognosis. In animal studies, brief periods of ischemia in noninfarct-related (nonculprit) coronary arteries protect the culprit myocardium via remote ischemic preconditioning. Positive fractional flow reserve (FFR) documents functional significant coronary nonculprit stenosis, which may offer remote ischemic preconditioning of the culprit myocardium. The aim of the study was to investigate the association between functional significant, multivessel disease (MVD) and reduced culprit final infarct size or increased myocardial salvage (myocardial salvage index [MSI]) in a large contemporary cohort of STEMI patients. Methods: Cardiac magnetic resonance was performed in 610 patients with STEMI at day 1 and 3 months after primary percutaneous coronary intervention. Patients were stratified into 3 groups according to FFR measurements in nonculprit stenosis (if any): angiographic single vessel disease (SVD), FFR nonsignificant MVD (functional SVD), or FFR-significant, functional MVD. Results: A total of 431 (71%) patients had SVD, 35 (6%) had functional SVD, and 144 (23%) had functional MVD. There was no difference in final infarct size (mean infarct size [%left ventricular mass] SVD, 9±3%; functional SVD, 9±3%; and functional MVD, 9±3% [ P =0.82]) or in MSI between groups (mean MSI [%left] SVD, 66±23%; functional SVD, 68±19%; and functional MVD, 69±19% [ P =0.62]). In multivariable analyses, functional MVD was not associated with larger MSI ( P =0.56) or smaller infarct size ( P =0.55). Conclusions: Functional MVD in nonculprit myocardium was not associated with reduced culprit final infarct size or increased MSI following STEMI. This is important knowledge for future studies examining a cardioprotective treatment in patients with STEMI, as a possible confounding effect of FFR-significant, functional MVD can be discarded. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01435408 (DANAMI 3-iPOST and DANAMI 3-DEFER) and NCT01960933 (DANAMI 3-PRIMULTI).